Análisis morfométrico del surco nasal en aves - Ibañez, Lucía Mariel (2010)
The location of the salt gland in birds can be supra- or infraorbital, leaving generally a mark on the skull. The first type leaves a mark on the frontals, the fossa glandulae nasalis or nasal furrow, placed in the interorbital region. The second type leaves an impressio glandulae nasalis in the antero-ventral side of the frontals. The shape of the nasal furrow of birds habitant of different environments belonging to several guilds was analyzed through a Fourier Elliptic Analysis and others related metric features. An outlines analysis of the fossa gl. nasalis was made in 18 species (marine, continental and ubiquitous taxa), and another one was applied to two skuas species distinguishing males from females. According to the obtained results, the outline of the nasal furrow is not related with the environment, and its length vary intra- and inter-specifically. Morphology and size of the nasal furrow are independent from sex in the Gentoo Penguin (Pygoscelis papua) and the South Polar Skua (Catharact maccormicki), while in the Brown Skua (Catharacta antarctica) differences in size were detected between males and females.